Provide Or Demonstrate? Legal Comparison On Migrant Protection In Indonesia And Hong Kong - Hera Susanti (Jurisprudensi : Jurnal Ilmu Syariah, Perundangan-Undangan dan Ekonomi Islam, 2020)
This article examines the weakness of legal protection system for Indonesian migrant workers which are still vulnerably exposed to the practice of human trafficking leading to many cases of physical, sexual and psychological exploitation of Indonesian migrant workers abroad. This study quantitatively explores the model of providing legal protection for Indonesian migrant workers in Hong Kong, China in order to improve legal protection for Indonesian migrant workers abroad. Finally this study finds the effectiveness and successfulness of the well-established legal system of Hong Kong’s government, as one of the most intended countries by Indonesian migrant workers, in providing protection and guaranteeing the rights of migrant workers. These models constitute the ideal Human Rights Protection schemes for the other countries in realizing strategy and policies for better regulation.